First description of B chromosomes in the Hyphessobrycon (Characiformes, Characidae) genus: a hypothesis for the extra element of Hyphessobrycon eques Steindachner, 1882 - Piscor, Diovani [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP] (Pensoft Publ, 2015)
The Hyphessobrycon are allocated in the incertae sedis group of the Characidae family, one of the genera with more species of the group. The chromosomes of some species of Hyphessobrycon are known, and the diploid number most common for genus is 2n = 50 chromosomes. The aims of this study were to examine the karyotype macrostructure in the Hyphessobrycon eques Steindachner, 1882, and show a new origin hypothesis for B chromosomes. The diploid number observed for H. eques was 2n = 52 chromosomes, and a karyotype formulae of 12m + 18sm + 8st + 14a, with FN (fundamental number) = 90 for both sexes. Only two females showed one B chromosome. The heterochromatin was observed mainly on centromeric regions, and in the long arm of the B chromosome. In this paper, the relationship of the B chromosome of H. eques with an occasional chromosome rearrangement was discussed.
Keywords: Karyotype; Supernumerary chromosomes; C-banding; Heteromorphism; Chromosome evolution